Peningkatan Hasil Belajar PKn Melalui Model Pembelajaran Student Team Achievement Division - Nidarwati Tanjung (JURNAL GLOBAL EDUKASI, 2020)
Abstract: The purpose of this study is to improve student learning outcomes in Class IVB SD Negeri 070976 Gunungsitoli, Gunungsitoli district on globalization material by applying the STAD type cooperative learning model. This research is a classroom action research conducted in two cycles. The subjects in this study were students of Class IVB of SD Negeri 070976 Gunungsitoli, Gunungsitoli district in the academic year 2017/2018, with 15 students consisting of 11 male students and 4 female students. Data collection techniques used are test and non-test techniques. Data analysis was performed with qualitative and quantitative data analysis. Indicators of the success of this study include the percentage of student learning activities of at least 75%, an average grade of ≥75 with a percentage of classical completion of at least 75%, and a minimum teacher performance score of 71 (B). Based on the implementation of the first cycle the teacher performance value of 83.08 (AB). In cycle II, the teacher's performance score increased to 89.17 (A). Student learning activities reached 65.12% and in the second cycle increased to 79.87%. In the first cycle, the average value of student learning outcomes reached 70.67 with the percentage of classical learning completion 66.67%. Meanwhile, in the second cycle the average value of student learning outcomes increased to 81.67 with the percentage of classical learning completion 93.33%.Keywords: Globalization, Student Team Achievement Division. Abstrak: Tujuan Penelitian ini yaitu untuk meningkatkan hasil belajar siswa Kelas IVB SD Negeri 070976 Gunungsitoli kecamatan Gunungsitoli pada materi globalisasi dengan menerapkan model pembelajaran kooperatif tipe STAD. Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan dalam dua siklus. Subjek dalam penelitian ini yaitu siswa Kelas IVB SD Negeri 070976 Gunungsitoli kecamatan Gunungsitoli tahun pelajaran 2017/2018, dengan jumlah 15 siswa yang terdiri dari 11 siswa laki-laki dan 4 siswa perempuan. Teknik pengumpulan data yang digunakan yaitu teknik tes dan non tes. Analisis data dilakukan dengan analisis data kualitatif dan kuantitatif. Indikator keberhasilan penelitian ini meliputi persentase aktivitas belajar siswa sekurang-kurangnya 75%, rata-rata nilai kelas ≥75 dengan persentase tuntas belajar klasikal sekurang-kurangnya 75%, dan nilai performansi guru minimal 71 (B). Berdasarkan pelaksanaan siklus I nilai performansi guru sebesar 83,08 (AB). Pada siklus II, nilai performansi guru meningkat menjadi 89,17 (A). Aktivitas belajar siswa mencapai 65,12% dan pada siklus II meningkat menjadi 79,87%. Pada siklus I, rata-rata nilai hasil belajar siswa mencapai 70,67 dengan persentase tuntas belajar klasikal sebesar 66,67%. Sementara itu, pada siklus II rata-rata nilai hasil belajar siswa meningkat menjadi 81,67 dengan persentase tuntas belajar klasikal sebesar 93,33%.Kata Kunci: Globalisasi, Student Team Achievement Division.